Contradictory and Intersecting Patterns of Inclusion and Exclusion of Street Youth in Salvador, Brazil - Ursin, Marit (2016)
Drawing on longitudinal qualitative research in Brazil involving participant observation and narrative interviews with young homeless persons, and semi-structured interviews with middle class residents, local businesses, and patrolling police officers, three overlapping yet contradictory dimensions of inclusion and exclusion are developed. First the hegemonic exclusionary discourse that tends to produce stigmatizing labels on poor people in general, and boys and young men on the street in particular, is mapped out. Second, socio-spatial exclusionary mechanisms involving architectural measures, surveillance cameras and violent policing, guarding the neighbourhood from stigmatised ‘others’ are examined. Third, the less recognised but equally important inclusionary mechanisms, facilitating street life and enabling a sense of belonging among young homeless people are explored. A simplistic and unidimensional conceptualisation of social exclusion is critiqued while demonstrating the multifaceted, intertwined, and contradictory character of homeless people’s social relationships with middle class residents, businesses, and police. Furthermore, the exclusion/inclusion dualism that is vivid in the existing literature is questioned. It is suggested that a nuanced picture is vital to increasing our understanding of the everyday lives of homeless populations and that further investigation and theorization of their exclusion as well as inclusion is needed.